Vnitřní akustika osobního automobilu - Prokšová, Lucie (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2017)
Práce se zabývá analýzou akustických vlastnosti vnitřního prostoru osobního automobilu pomocí metody konečných prvků. Součástí práce je analýza budicích účinků od jednotlivých zdrojů vibrací a vyhodnocení odezvy ve vnitřním akustickém prostoru kabiny se zaměřením na pasažéry vozidla a problematika návrhu vhodných konstrukčních úprav za účelem snížení hluku v kabině.

The thesis is focused on the analysis of the acoustic properties of the interior of the passenger car by using the finite element method. Part of the work is an analysis of the excitation effects of individual vibration sources and the evaluation of the response in the interior of the cabin with a focus on the passengers of the vehicle and also solving the problem of the design of structural modifications in order to reduce the noise inside the cabin.
Passenger Car Internal Acoustics
Keywords: akustika; vibrace; hluk; automobil; metoda konečných prvků; Octavia RS combi; acoustics; vibration; noise; automobile; finite element method; Octavia RS combi